Are cytokeratin‐positive cells in sentinel lymph nodes of patients with invasive breast carcinomas up to 5 mm usually insignificant?. Issue 2 (9th January 2015) - Jaffer, Shabnam; Bleiweiss, Ira J; Nayak, Anupma
<x xml:space="preserve">Abstract</x> Aims It is known that sentinel lymph nodes (SLN) may be falsely positive due to displaced epithelial cells, particularly in cases with an underlying intraductal papilloma. Given the low metastatic rate in pT1a carcinomas, we aimed to investigate the effect of this phenomenon on staging. Methods and results Using morphology and immunohistochemistry, we classified the epithelial cells in the SLN in 39 cases of pT1a carcinoma as positive for carcinoma in six, negative in 26 and undetermined in seven. Comparative morphology and immunohistochemistry (using oestrogen receptor, ER) showed complete concordance between the primary carcinoma and SLN in the positive cases, and discordance in the negative cases. The primary tumours in the negative cases were ER‐positive except one, in contrast to the SLN cytokeratin‐positive (CK+) cells, which were ER‐negative. The exception was a case with a Her2‐positive primary, in which the SLN CK+ cells did not stain for Her2. In these cases considered SLN‐negative, either displacement (19 cases) or an intraductal papilloma (20 cases) was identified. Two cases showed displacement of benign and malignant cells in the biopsy. Seven cases were indeterminate due to the small number of SLN CK+ cells, precluding comparison with the primary. Conclusion Given the low rate of metastases in pT1a carcinomas, the significance of SLN CK+ cells should be resolved by comparative morphology and immunohistochemistry to prevent erroneous upstaging.